Study of the allelic frequency of HSPA6 gene and its genotypes and their effect on some characteristics of milk production in Holstein cows - Abdullah Hamid Salem; Ghadeer Razak Ahmed (University of Thi-Qar Journal of agricultural research, 2022)
The study was conducted at the Taj Al-Nahrain cattle station in Al-Diwaniyah Governorate, which is 200 km from the center of Dhi Qar Governorate. For the period from 10/15/2021 to 10/3/2022, 49 Holstein cows imported from Germany were used in this experiment, all in the third production cycle. And the laboratory part of the study was conducted in the laboratory of the Marsh Research Center \ Dhi Qar University for the purpose of separating the genetic material from cow blood samples and conducting genetic analysis on it and extracting the possible genotypes HSPA6 heat shock protein gene. The animals in the station were fed according to the season and the year in terms of the availability of fodder and the percentage of costs involved in raising the cows, as well as on the general state of the productivity of the cows, but in general they are provided with green fodder, which includes jet, barley, corn stalks and a percentage of each of the dry fodder (hay and hay). ) and concentrate (barley, bran and cake) according to what is available from them, as well as limestone and table salt. Data on milk production were collected from the station records, where the milk production was recorded weekly for the morning and evening fenugreek by the station, and the milk components were analyzed in the Abu Dairy Company Gharib / Research and Development Division by Milk Analyzer. 3 ml of blood was collected from the udder vein of each cow by 5 ml medical syringes, suitable for the size of the animal’s vein, and placed in collection tubes containing an anticoagulant substance (K2 EDTA) and transported in a cooler box for safekeeping Freezing at -18°C until extraction time.From the results obtained from this study, we can conclude that the mutation detected in the studied segment of the 6HSPA gene was a type of missense mutation and worked to change the code of the amino acid valine to the code of the amino acid leucine. Three genotypes were shown: GG, GT, and TT. It was found that there was a clear commonality of cows carrying the GG genotype with a rate of 88%, followed by the GT genotype with 8%, while the TT genotype got the lowest percentage and amounted to 4%, and with allelic recurrence Its value is 0.92 for the G allele and 0.08 for the T . alleleGroups of cows carrying the genotypes (GG, GT and TT) did not differ significantly among themselves in the characteristics of milk production and its components, but an arithmetic superiority between the three genotypes was observed and referred to in all the studied traits.